Dissolution thermodynamics and preferential solvation of genistein in some (ethanol + water) mixtures at different temperatures. (3rd October 2022) - Nan, Guanjun; Huang, Yanru; Liu, Zhengzheng; Liu, Yu; Li, Yunzhe; Yang, Guangde
Abstract: The solubility of genistein was measured in the binary system of ethanol and water at temperatures ranging from 288.2 to 328.2 K. The obtained data were correlated with the modified Apelblat model, Yalkowsky model, λh model, CNIBS/R-K model, Jouyban-Acree-van't Hoff model, and modified Wilson model and their prediction accuracy was evaluated by calculating the mean relative deviation. The thermodynamic functions, Gibbs energy, enthalpy, and entropy of solution were determined using van't Hoff equation. Moreover, the preferential solvation was analyzed by using the solubility data at 298.2 K. The solubility of genistein in the system increased with an increase in temperature and mole fraction of ethanol in the solvent mixtures. The values for solubility of genistein are ranging from 0.47 obtained in neat water at T = 288.2 K to 5.02 obtained in absolute ethanol at T = 328.2 K. The values of Δ soln G, 0 Δ soln H 0 and Δ soln H 0 for the dissolution of genistein in mixtures are positive, whereas the values of Δ soln H 0 in neat water and absolute ethanol are negative. The thermodynamic properties of dissolution suggest that the dissolution process is non-spontaneous and endergonic. The modified Apelblat model can provide more accurate predictive solubility of genistein in the water and ethanol mixtures, whereas Yalkowsky model calculates solubility of genistein with large deviations. Genistein is preferentially solvated by water in water-rich mixtures (0 < x 2 < 0.24) but preferential solvation by ethanol in the region of 0.24 < x 2 < 1. Overall, this work could be applied for designing and optimizing the extraction, purification, and crystallization process of genistein.